On the Quantitative Assessment of Perceived Housing in Later Life. - Oswald, Frank; Kaspar, Roman (Journal of Housing for the Elderly)
Person-environment relationships become particularly important in later life. Our discussion of challenges in the assessment of experiential person-environment exchange processes is grounded on a four-domain model of perceived housing. We present empirical findings from an iterative process of instrument revision seeking optimization of both reliability and validity issues regarding control-related and meaning-oriented domains of perceived housing. Our initial reconstruction, however, was not confirmed to represent a consistent and reliable measure for the suggested dimensions of housing-related identity, privacy, and autonomy. Exploratory post-hoc analyses of the pilot pool of indicators suggests six holistic facets, such as “daily independence” “neighborhood belonging”, “mirror of self”, “continuity and remaining in place” and “being alone and at peace”. Plausible content-related interpretation and relations to major background characteristics encourage the continuous task of tailoring assessment instruments to meet the holistic character of housing experiences in later life.